Identification and Diagnosis of Foetal Alcohol Spectrum Disorder (FASD) in Children at High Risk of Prenatal Alcohol Exposure: A Service Evaluation - Holly Dawson; Suvidhi Khurana; Milla McNally; Amanda Waldman; Rani Samuel (BJPsych Open)
Aims: Prenatal alcohol exposure (PAE) is a leading preventable cause of neurodevelopmental, mental health, and cognitive difficulties. This study evaluates the identification of Foetal Alcohol Spectrum Disorder (FASD) in a high-risk cohort of adopted and Children In Care (CIC) of the local authority, referred to Symbol Team, a specialist Tier 3 service for Children Looked After (CLA) and Adopted young people within Lewisham Child and Adolescent Mental Health Service (CAMHS).